2019
DOI: 10.34108/eujhs.485845
|View full text |Cite
|
Sign up to set email alerts
|

Hemşi̇reli̇k Öğrenci̇leri̇ni̇n Hasta Güvenli̇ği̇ Konusundaki̇ Bi̇lgi̇ Düzeyleri̇

Abstract: ÖZ Giriş: Bu çalışma, hemşirelik öğrencilerinin hasta güvenliği konusunda bilgi düzeylerini belirlemek amacıyla yapılmıştır. Gereç Yöntem: Araştırmanın evrenini bir üniversitenin hemşirelik bölümünde öğrenim gören ikinci, üçüncü ve dördüncü sınıf öğrencileri oluşturmuştur. Örneklem seçiminde evrenin tamamına ulaşılması hedeflenmiştir. Çalışma sonunda evrenin %79'una ulaşılarak 551 öğrenci ile çalışma tamamlanmıştır. Veriler anket formu ile toplanmıştır. Etik kurul onayı, kurum izni ve bireylerden yazılı olur a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

1
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(9 citation statements)
references
References 9 publications
1
8
0
Order By: Relevance
“…4 Moreover, it has been reported that these harms lead to injury, complications, recurrence or disruption of diagnosis and treatment, loss of confidence in healthcare personnel, increased hospital stay, and deaths in patients. 6,7 Therefore, patient safety is pivotal for maintaining quality health care.…”
mentioning
confidence: 99%
See 4 more Smart Citations
“…4 Moreover, it has been reported that these harms lead to injury, complications, recurrence or disruption of diagnosis and treatment, loss of confidence in healthcare personnel, increased hospital stay, and deaths in patients. 6,7 Therefore, patient safety is pivotal for maintaining quality health care.…”
mentioning
confidence: 99%
“…Patient safety culture is possible by developing knowledge, attitudes and behaviors related to patient safety throughout the professional life, starting from the health education process. 6,7 When studies on patient safety culture are examined, it has been reported that patient safety training given to healthcare professionals positively affects patient safety knowledge, attitudes and skills. 8,9 In addition, the WHO has included nurses, midwives, and other health professionals in the "WHO Patient Safety Curriculum for Medical Schools" guideline that launched for medical students.…”
mentioning
confidence: 99%
See 3 more Smart Citations